Peran Guru Pendamping Khusus dalam Mewujudkan Kelas Inklusif yang Efektif - Khairotul Nur Indah Wadria; Damri Damri; Mardhatillah Zulpiani (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This article discusses the role of Special Assistant Teachers (GPK) in creating an effective inclusive classroom, where all students, including children with special needs, can participate optimally in the learning process. GPK plays the role of facilitators, mediators, and regular teacher partners in accommodating diverse learning needs. This role is realized through individual needs assessments, adjustment of learning strategies, modification of teaching materials, and provision of academic and social-emotional support to students. The results of the study show that the success of inclusive education is greatly influenced by GPK's professional competence, especially in understanding the characteristics of children with special needs and implementing differentiatory learning. In addition, effective collaboration between GPK and regular teachers is a key factor in creating an inclusive and non-discriminatory learning environment. Institutional support, such as inclusive school policies, the availability of infrastructure, and the support of school leaders, also play an important role. This article emphasizes the need for sustainable professional development, clear division of duties, and supportive education policies to strengthen GPK's role in promoting inclusive education equity in Indonesia.